EFEK PROGRAM REVITALISASI PADA PASAR GEDE HARJONAGORO DI KOTA SURAKARTA SEBAGAI BENTUK MEMAJUKAN EKONOMI KERAKYATAN - Itok Dwi Kurniawan (RESEARCH FAIR UNISRI, 2022)
This reseacrh focuses on analyzing the effects of a market revitalization program on traditional markets in Surakarta City. Surakarta City is one of the cities in Central Java province that cares about the preservation of traditional culture. Traditional culture for the government and society of Surakarta is the basis of regional development. So that the realization in maintaining this traditional culture is by revitalizing traditional markets in Surakarta. Market revitalization is a manifestation of a people's economy that involves the role of the state in advancing traditional markets. Market revitalization is an improvement from the condition of the market which initially did not have complete facilities and was remodeled into a traditional market that has the latest characteristics. This program is used to improve quality in traditional markets in order to compete with modern markets. Pasar Gede is the target place for market revitalization. Pasar Gede is one of the oldest and largest markets in Surakarta City. The results of the research theoretically obtain information that there is a positive effect in the form of increasing income for traders in the market because it attracts consumers with new buildings and completeness of goods sold in it. However, there are also negative effects, namely in the form of conflicts that occur due to differences of opinion between traders and the government. Therefore, there will be some suggestions presented in this article.